Pengaruh Zakat dalam Peningkatan Kesejahteraan Masyarakat Indonesia - Pribadi Rere, Laode Muh. Nanang (Syntax Literate, 2026)
Zakat as one of the social financial instruments in Islam has an important role in improving the welfare of the community, especially in Indonesia where the majority of the population is Muslim. This article examines the influence of zakat on improving the welfare of the Indonesian people through various distribution and utilization mechanisms. Data are obtained from a variety of relevant primary and secondary sources, as well as descriptive and comparative analysis. Using qualitative methods, the approach used, namely, literature studies and secondary data analysis from amil zakat institutions, BPS, as well as various journals and related reports. The results of the study show that zakat can significantly reduce poverty, increase access to education, health, and economic empowerment of the underprivileged.